Marlein van Raalte, Rhythm and Metre. Towards a Systematic Description of Greek Stichic Verse, Assen-Maastricht-Wolfeboro, Van Gorcum, 1986, 463 pp. ISBN 90-232-2229-6 (Minerva, 2019)
Review: Marlein van Raalte, Rhythm and Metre. Towards a Systematic Description of Greek Stichic Verse, Assen-Maastricht-Wolfeboro, Van Gorcum, 1986, 463 pp. ISBN 90-232-2229-6